CATALYTIC SYNTHESIS OF DIVINYL FROM ETHANOL - D.S. Abdimurodova; N.I. Fayzullayev (Western European Studies, 2025)
This study investigates the catalytic conversion of ethanol to divinyl under atmospheric pressure and temperatures ranging from 473 to 573 K in a flow-type reactor. Catalysts composed of magnesium, zirconium, and lanthanum oxides supported on SiO₂ were employed. The main products identified during ethanol dehydrogenation were acetaldehyde, methane, and carbon monoxide, alongside minor secondary products such as divinyl, methyl ethyl ketone, butanal, and butanol. The catalytic performance and selectivity were found to depend on both the reaction conditions and the catalyst composition. Mechanistic analysis showed that Lewis acid sites promote aldol condensation of acetaldehyde. IR spectroscopy was used to characterize the active centers of the catalysts, particularly for MgO/SiO₂ and ZrO₂–FeO– ZnO/SiO₂ systems. The results contribute to a better understanding of the reaction pathways and the design of selective catalysts for divinyl production from ethanol.
Keywords: ethanol; catalytic synthesis; divinyl